Integration of the Wahdah Method and the Takrir Method in Tahfiz Alquran Learning - Nudri, Divsi Aprilia; Zulfajri, Zulfajri (STIT Ahlussunnah Bukittinggi, 2025)
This study was motivated by the limited research on the integration of the Wahdah and Takrir methods in Alquran memorization learning at the madrasah tsanawiyah level, even though these methods play an important role in improving the quality and quantity of students' memorization. This study aims to analyze the process of applying the integration of the Wahdah and Takrir methods, the results of their application on students' memorization abilities, as well as the supporting and inhibiting factors in the Hubbul Quran Tahfidz Madrasah Program at Madrasah Tsanawiyah Negeri 6 Padang. This study uses a qualitative approach with a field research design. Data were obtained through interviews, observations, and documentation of program leaders, tahfidz teachers, and students selected purposively, then analyzed descriptively and qualitatively. The results showed that the integration of the Wahdah and Takrir methods was applied systematically and complemented each other, where Wahdah formed new memorization and Takrir strengthened and stabilized memorization. The application of this method was proven to improve the quantity of memorization, reading quality, tajwid accuracy, and students' memory. The success of the application was supported by teacher competence, infrastructure, a conducive learning atmosphere, and student motivation, while the main obstacles included limited learning time and a lack of parental guidance at home. The conclusion of this study confirms that the integration of the Wahdah and Takrir methods effectively improves the quality of tahfidz learning when supported by the synergy between schools, teachers, students, and parents.